ExpressO (express beverage blender) / Nor Yusra Izzati Ahmad Shafiei...[et al.] - Ahmad Shafiei, Nor Yusra Izzati; Kamarul Ariffin, Nurul Haziqah; Azmi, Siti Maisarah; Sallehudin, Siti Umairah
Nowadays, people are concerning about time saving, Our ExpressO (Express Beverage Blender) is a kitchen appliance used to mix beverages. ExpressO (Express Beverage Blender) consists of a blender container with a rotating metal blade at bottom, powered by motor in the base electric base. This blender also can crushes ice. This innovative blender are the blender that combined two features which is Coffee - Pod Blender Machine (have a coffee brew machine diffuser) which is direct to brew system and Flavor - Pod blender Machine (fruits/cordial blending machine diffuser). The blender can diffuse the own flavor only with one button, there are some function included have a few compartment that can be filled by various flavor for blended beverages. Then, the other features are auto- flavor making with only one button we can choose either we want hot brewing coffee or icy various flavor blended beverages. Because of the two option of beverages, it shows that this ExpressO (Express Beverage Blender) can produce hot/cold drinks. ExpressO (Express Beverage Blender) also easy to clean once has been used this is because we only have to unattached the blender container parts only without worrying the motor in the electric base will affected during the cleaning session. In order for practical and time saving during the beverages preparation, we come up with new ideas. The competitve advantages for this product are, this product will be useful for working individual, family and beverages line industry because has many advantages. For example they should invest on innovative blender which is the blender can diffuse the own flavor only with one button without required the barista * measure the ingredient for the beverages first. Here is the situation: The innovative blender has a few compartment that can store the beverage's flavor. So, with the only one clicks on the desired beverage's flavor button for example Ice Latte, then, the beverages will ready within 3 minutes without wasting barista's time to finding, measure and prepare the ingredients. With this innovation, this will makes the services faster and the output of the product will increase. Hence, if the output increase the input will increase too.